Usefulness of vestibular evoked myogenic potentials in diagnosis of peripheral vestibular disorders - Sirige, Sreelatha; Kumar, S. Rajesh; Chaitanya, V. Krishna; Reddy, Vasu Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Vestibular evoked myogenic potentials (VEMP) are electromyographic responses to high-intensity acoustic stimuli to test vestibular system, otolith function and integrity of inferior vestibular nerve. These are easy to perform and non-invasive. In this study, we aimed at clinical application of VEMP to evaluate common peripheral vestibular disorders. Methods: Prospective observational study carried in ENT department during January 2015-November 2016 over 40 patients in age group between 30-70 years with history of vertigo who underwent regular neuro-otological examination and VEMP. Results: Of these, 25 diagnosed with BPPV, 11 with Meniere’s disease, and four with vestibular neuritis. Eight patients showed delayed VEMP responses. 28 (70%) patients had normal VEMP, 12 (30%) had abnormal VEMP responses. Out of 25 patients suffering from benign paroxysmal positional vertigo (BPPV) posterior semi-circular canal was involved in 20 (80%) patients and lateral semi-circular canal in 5 (20%) patients. Abnormal VEMP was found in 5 (20%) patients involving posterior semi-circular canal and in 1 (20%) patient involving lateral semi-circular canal. In patients with Meniere’s disease stage I, Meniere’s disease was observed in 7 (63.6%), stage II in 2 (18.1%), and stage IV disease in 1 (9.09%) patient. In these patients, abnormal VEMP was found in 3 (42.8%) of 7 stage I, 1 (50%) of 2 stage II and 1 (100%) of stage IV patients. One (20%) patient had abnormal VEMP responses during study. Conclusions: VEMP are short-latency EMG that evaluates saccule and inferior vestibular nerve in peripheral vestibular nervous system. VEMP should be considered as complementary test along with conventional vestibular function tests in patients with peripheral vertigo.